Lichens: A myriad hue of Bioresources with medicinal properties - Ramya K; Thirunalasundari Thiyagarajan (International Journal of Life Sciences, 2017)
Lichens form an ideal model to study its bioactive metabolites. A symbiotic association between fungus and a chlorophyll containing partner; the green algae or cyanobacteria, and sometimes both together form lichens. Lichens are important species for several reasons. The unique and biologically active substances present in the lichen thalli contribute to several important medicinal values of lichens like antiviral, antibacterial, antifungal, antioxidant, cytotoxic effect and many more. All these manifold activities of lichen metabolites represent the therapeutic potential of lichens that has a great impact in Pharma industries. The present article is a review on the importance of lichens in contributing towards valuable resources emphasising on its medicinal properties.